The impact of R&D activities on exports of German business services enterprises: First evidence from a continuous treatment approach - Alexander Vogel; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This study uses newly available representative data from German business services firms and a continuous treatment approach based on the generalized propensity score to test for a causal effect of R&D activities (measured by the share of engineers and natural scientists in all employees) on the share of exports in total sales. We find evidence for a positive and statistically significant but small causal effect. This result is in line with the (non-causal) results reported in Vogel and Wagner (2012) based on regression models with and without control for unobserved time-invariant firm characteristics. The bottom line, then, is that R&D activity does matter for success of German business services firms on export markets - but not much.
Keywords: F14; 330; innovation; export; business services; Germany; Unternehmensdienstleistung; Innovation; Forschung; Export; Internationaler Dienstleistungsverkehr; Deutschland